Proposal for a graded approach to disclosure of interests in accredited CME/CPD. Issue 1 (1st January 2015) - Griebenow, Reinhard; Campbell, Craig; Qaseem, Amir; Hayes, Sean; Gordon, Jennifer; Michalis, Lampros; Weber, Heinz; Pozniak, Eugene; Schäfer, Robert
Abstract : Disclosing conflicts of interest (COIs) is an important step in the management of COIs and is considered to be crucial to the trustworthiness of presenters. There are significant variations in disclosure procedures regarding the following: a. How COI is assessed in declaration forms (e.g. type of question, respondent awareness) b. Type of relationships c. Detailing of information to program committee members These variations in procedures have in effect led to a. Underreporting of COI b. Reducing the informational value of declared COI to participants Thus, it has been the aim of the authors to propose a basic formula for a minimum standard declaration of financial COI, with the potential to be applicable to all types of accredited continuing medical education (CME) as well as to all individuals (e.g. speakers, authors) involved in planning and conduct of CME activities. This approach should also serve as basis for more elaborate disclosures as well as strategies for management of conflict of interests adapted to the risk of bias. Furthermore, we also propose a basic set of items to be declared as nonfinancial interests.